Determining Cognate Level and Century Split between Banjar and Malay Languages: A Historical and Comparative Linguistic Study: (Penentuan Tingkat Kekerabatan dan Abad Pisah antara Bahasa Banjar dengan Bahasa Melayu: Kajian Linguistik Sejarah dan Perbandingan) (Jurnal Bahasa, 2021)
Banjar is an Austronesian language spoken by the Banjar tribe in Kalimantan, Indonesia as a mother tongue. The Banjar is hypothesized to be a proto-Malayik language, similar to the Minangkabau, Malay and Iban languages. This study will examine the cognates' level between Banjar and Malay language by listing the basic vocabulary of both languages; using lexicostatistical comparison and glottochronology method. This method determines the percentage of cognate words by calculating the number of cognate words through the studying the elements of retention and innovation. This basic vocabulary survey and listing will make use of Morris Swadesh's list of 200 words. Out of 195 basic vocabularies compared, 158 or 81.0% of the basic vocabularies of the Banjar are cognate with the Malay. Based on this percentage, it shows that Banjar and Malay are cognates. The century split between both languages from 2021 is assumed to be between the 15th century to the 17th century or around 1440 to 1602 years ago. Regardless the fact, the Banjar language could not be understood by Malay speakers unless it is learnt by them. The findings of this study prove that the lexicostatistical and glottochronological methods as suggested by Lees (Lehman, 1973: 105) and Gudschinsky (1964: 618) in determining the century split of Austronesian language is relevant and appropriate in systematically describing hypothetical age-based language genealogy as presented by Asmah (2008: 3) and other local researchers.